2018
DOI: 10.4103/jehp.jehp_51_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dental erosion on oral health among employees of battery-manufacturing units in Baddi, Himachal Pradesh, India

Abstract: OBJECTIVE:The objective of the study was to obtain data on prevalence and severity of dental erosion among acid industry workers in Baddi (Himachal Pradesh).MATERIALS AND METHODS:A cross-sectional study was conducted among 800 battery industry workers. The demographic details were recorded on a prestructured pro forma. Type III examination was done. Dental erosion was recorded based on the index given by Bardsley (simplified scoring criteria for tooth wear index). Appropriate statistical tests were used to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This could be due to the high education level, occupation, and income levels of the study participants. Dental erosion was found in 2.5% of participants; in contrast, 49% of the industrial workers had dental erosion in Himachal Pradesh (Bansal, Singh, Bector, & Dogra, 2018). These differences could be due to the nature of industrial work and exposure to chemicals at workplace.…”
Section: Discussionmentioning
confidence: 93%
“…This could be due to the high education level, occupation, and income levels of the study participants. Dental erosion was found in 2.5% of participants; in contrast, 49% of the industrial workers had dental erosion in Himachal Pradesh (Bansal, Singh, Bector, & Dogra, 2018). These differences could be due to the nature of industrial work and exposure to chemicals at workplace.…”
Section: Discussionmentioning
confidence: 93%
“…17 Examination of 800 battery workers at the production line in the Baddi city showed that 48% had dental rosion. 18 In all these studies the dental erosion and other oral pathologies were significantly higher in workers at the production line than the controls at the nonproduction line. Tuominen et al, (1991) conducted a survey in Tanzanian fertilizer factories on 68 acid workers exposed to high concentrations of sulfuric acid fumes.…”
Section: Epidemiology and Dental Healthmentioning
confidence: 85%
“…12,13 Recently (2014-2018) some studies on battery factories hazards from different cities in India have been published. [14][15][16][17][18][19] China, Japan, and South Korea are the main battery producers.…”
Section: Epidemiology and Dental Healthmentioning
confidence: 99%
“…[ 3 ] (18.4%), but with other studies done by Bansal et al . [ 14 ] (48.6%), Yusuf et al . [ 15 ] (49.5%), Kundu et al .…”
Section: Discussionmentioning
confidence: 99%